Prevalensi dan faktor determinan kejadian stunting pada siswa sekolah dasar di Kota Subulussalam, Provinsi Aceh 2021 - Nasrul Z Nasrul Z; Said Usman; Alfridsyah Alfridsyah (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2022)
Subulussalam City has always been in the top three with the highest stunting rate in Aceh from 2013-to 2021. This study aims to determine the prevalence and determinants of stunting in primary school students. The study used a case-control design with a sample of 30 stunted children and 60 non-stunted control children. Interview data and measurement of height with microtoise. Stunting data was processed using WHO AnthroPlus software. Statistical analysis using Odds Ratio test and Binary Logistic Regression. The result, the prevalence of stunting in Sultan Daulat is 24%. The determinants of stunting are the mother's occupation (as a farmer) p= 0,035 and OR= 98.9, the father's job is not fixed (a laborer) p = 0.046 and OR= 22,9, and the incidence of diarrhea (p= 0,047; OR= 17,9), and low birth weight (p= 0,047; OR= 0,78). In conclusion, children with diarrhea and low birth weight are triggers for children to experience stunting, while sanitation conditions and drinking water consumed have no effect on stunting. Children who are stunted are more commonly found in mothers with a history of giving birth <20 years and >35 years.